The Use of Diary Writing to Improve The Writing Skills of Eight Grade At MTs S Madinatussalam - Ayu Farah Cintya; Irma Damayanti Lubis; Netti Pevvi Yanti; Zahara Safrina Aini Lubis (MUDABBIR Journal Reserch and Education Studies, 2022)
This study focuses on problem solving in class and obtains research results that writing diaries can improve students' writing skills. This research was conducted in two cycles and is an action research. The subjects in this study were students of class VIII Mts S Madinatussalam, with a total of 30 students. The instruments used in collecting data are tests and field observations. After implementing diary writing in two types of texts, namely descriptive and recount texts, the researcher then analyzed the collected data, and found that the students' grades gradually increased, especially when writing recount texts. In the first cycle the researcher found two weaknesses; namely the slowness of students submitting their diaries which made researchers late in providing feedback, and the limited vocabulary of students so that they tend to use simple sentences and the same vocabulary. Responding to these weaknesses, researchers used a reward strategy. In addition, the researcher also carried out activities to write works in pairs in the second cycle so that students learned from their friends.